Pemanfaatan Pati Kulit Pisang Kepok (Musa paradisiaca L.) dengan Penambahan Kitosan dan Gliserol sebagai Bahan Alternatif Pembuatan Bioplastik - Anisa Aprilia; Melfa Aisyah Hutasuhut; Leni Widiarti (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2026)
This study aimed to determine the characteristics of bioplastics derived from kepok banana peel starch (Musa paradisiaca L.) and to evaluate the quality of the bioplastics through tensile strength, elongation, and biodegradation tests. The research employed a laboratory-based experimental method starting with the extraction of starch from kepok banana peels followed by the production of bioplastics. Subsequently, physical and mechanical characterization tests were conducted, including tensile strength, elongation, and biodegradation analyses. The results indicated that the produced bioplastics exhibited a dark brown color, were odorless, and had a rough texture on the lower surface and a smooth texture on the upper surface. The mechanical testing showed that the highest tensile strength value obtained was 0.4117 MPa, while the highest elongation value reached 45.5%. Furthermore, the biodegradation test conducted over 21 days demonstrated a degradation rate of 93.99%. In conclusion, kepok banana peel starch with the addition of chitosan and glycerol shows significant potential as an environmentally friendly alternative material for the production of biodegradable bioplastics. Keywords: Bioplastic, Chitosan, Glycerol, Kepok Banana Peel Starch